2022
DOI: 10.1111/jpc.16029
|View full text |Cite
|
Sign up to set email alerts
|

Late presenting developmental dysplasia of the hip after a normal hip ultrasound at 6 weeks of age: A report of two cases

Abstract: Developmental hip dysplasia (DDH) is a paediatric condition in which the ‘ball and socket’ hip joint fails to form properly during infancy. The increased mechanical stress on the hip joint from DDH can contribute to the development of osteoarthritis during adulthood. Therefore, careful physical examination and imaging of all infants to diagnose DDH is critical to provide the best possible functional outcome. Ultrasonography (US) is a useful diagnostic test in providing a real‐time evaluation and three‐dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Pan et al . ( 22 ) also reported two cases of late presenting DDH in breech infant girls after normal hip ultrasound performed at 6 weeks of age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pan et al . ( 22 ) also reported two cases of late presenting DDH in breech infant girls after normal hip ultrasound performed at 6 weeks of age.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, literature has highlighted the possibility of a “late DDH” diagnosis after a negative initial ultrasound screening in children with breech presentation ( 16 22 ). If this condition were to be confirmed, there would be a group of children for whom current screening programs might not be sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, universal screening results into overtreatment of hips which would mature normally without any treatment. On the other hand, it has also been shown that some hips seem normal in the initial US examination but later require operative treatment despite the universal ultrasound screening [ 18 ]. These findings challenge the traditional linear pathophysiological model of hip joint development.…”
Section: Natural Progression Of Ddhmentioning
confidence: 99%
“…Before implementation of universal US to wider use, a more rigorous investigation of its benefits is required, as currently, the evidence does not promote the use of it. This can be explained by the extrinsic factor affecting the development of the hip joint after birth and thus initial screening during the early weeks cannot find these cases [ 17 , 18 ]. Also, the late detection and operative treatment rates with universal screening were similar to those among selectively and clinically screened newborns [ 2 ].…”
Section: Costs Effectiveness and Health Care Resourcesmentioning
confidence: 99%